Professional Identity in Chilean Translation Trainees: Initial Positioning, Perceptions and Valuations - Singer, Néstor; López, Vania; Basaure, Rosa (Íkala, Revista de Lenguaje y Cultura, 2020)
Affective development in translator education is an issue that has been under-researched (Hubscher-Davidson, 2018), particularly the development of professional identity in translator training. This article aims to present a phenomenological study on the development of translator trainees’ professional identity during their training. This study examines their narratives about their self-descriptions and perceptions on the professional translator and their training up to the start of this study, i.e. March 2018. To do this, semi structured interviews were conducted with a group of nine third-year translation trainees in a translation studies undergraduate Chilean programme. Results show that students 1) describe themselves and shy, insecure individuals who find it difficult to socialise, 2) present an idealised vision of the professional translator which clashes with their self-perceptions, 3) experience an emotional conflict between the fear to alterity and their agency to fulfil their academic and personal commitments, and 4) value their training positively. It is concluded that these elements constitute and additional input to plan translation course units in later stages of the programme.